Does hedonism influence real estate investment decisions? The moderating role of financial self-efficacy - Sharmila Devi R; Swamy Perumandla (Cogent Economics & Finance, 2023)
AbstractThe goal of this paper is to emphasize the importance of prioritizing pleasure and enjoyment in the properties being invested in over financial returns. This research aims to determine the impact of hedonism on an individual’s real estate investment decisions, with financial self-efficacy acting as a moderator. The study employs a quantitative, cross-sectional research approach, and data was collected from retail investors (homeowners and prospective home buyers) using a structured questionnaire. A total of 375 responses were obtained through snowball sampling. Further, PLS SEM was taken into consideration to test research hypothesis. The study’s findings indicate that an individual’s hedonism value has a significant positive influence on real estate investment decisions. Moreover, we found that financial self-efficacy has a significant negative impact on hedonism and real estate investment. One possible reason is that individuals with high financial self-efficacy may be more likely to analyse the financial details of a real estate investment carefully and make decisions based on a well-informed understanding of the potential returns and risks. It has also been observed that both age and income contribute positively to the decision to invest in real estate. This means that a young person is more likely to make risky investments like buying real estate stocks, land, etc. When individuals become older, real estate investment in the form of houses increases in order to provide a secure and comfortable living space for themselves and their families. Finally, when income rises, individuals seem to be looking for a comfortable life, pleasure, happiness, and social recognition, which significantly influence the real estate investment decision.